Where will the dhole survive in 2030? Predicted strongholds in mainland Southeast Asia - Tananantayot, Jiratchaya; Agger, Cain; Ash, Eric; Aung, Saw Soe; Baker-Whatton, Megan C.; Bisi, Francesco; Clements, Gopalasamy Reuben *; Cremonesi, Giacomo; Crouthers, Rachel; Frechette, Jackson L.; Gale, George A.; Godfrey, Alexander; et al. (Wiley, 2022)
Dhole (Cuon alpinus) is threatened with extinction across its range due to habitat loss and prey depletion. Despite this, no previous study has investigated the distribution and threat of the species at a regional scale. This lack of knowledge continues to impede conservation planning for the species. Here we modeled suitable habitat using presence-only camera trap data for dhole and dhole prey species in mainland Southeast Asia and assessed the threat level to dhole in this region using an expert-informed Bayesian Belief Network. We integrated prior information to identify dhole habitat strongholds that could support populations over the next 50 years. Our habitat suitability model identified forest cover and prey availability as the most influential factors affecting dhole occurrence. Similarly, our threat model predicted that forest loss and prey depletion were the greatest threats, followed by local hunting, non-timber forest product collection, and domestic dog incursion into the forest. These threats require proactive resource management, strong legal protection, and cross-sector collaboration. We predicted <20% of all remaining forest cover in our study area to be suitable for dhole. We then identified 17 patches of suitable forest area as potential strongholds. Among these patches, Western Forest Complex (Thailand) was identified as the region's only primary stronghold, while Taman Negara (Malaysia), and northeastern landscape (Cambodia) were identified as secondary strongholds. Although all 17 patches met our minimum size criteria (1667 km2), patches smaller than 3333 km2 may require site management either by increasing the ecological carrying capacity (i.e., prey abundance) or maintaining forest extent. Our proposed interventions for dhole would also strengthen the conservation of other co-occurring species facing similar threats. Our threat assessment technique of species with scarce information is likely replicable with other endangered species.